2004
DOI: 10.1007/s00535-003-1361-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prevalence of GB virus C, SEN virus, and HFE gene mutation in Japanese patients with nonalcoholic steatohepatitis

Abstract: Higher serum AST and ferritin, and lower serum T-Chol are distinctive features in NASH when compared with simple steatosis. GBV-C infection, SENV infection, and HFE gene mutation were not considered to influence the development of NASH from simple fatty liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
(80 reference statements)
1
17
1
Order By: Relevance
“…Hepatic iron overload thought to be associated with HFE gene mutations [10,11]. A significantly higher prevalence of HFE mutations in NASH patients has been reported as a factor responsible for liver fibrosis by increasing hepatic iron deposition [14,32], but recent studies have failed to confirm this [33][34][35]. In our study the prevalence of hyperferritinemia was significantly higher in the NASH patients than in patients with simple steatosis.…”
Section: Discussioncontrasting
confidence: 66%
“…Hepatic iron overload thought to be associated with HFE gene mutations [10,11]. A significantly higher prevalence of HFE mutations in NASH patients has been reported as a factor responsible for liver fibrosis by increasing hepatic iron deposition [14,32], but recent studies have failed to confirm this [33][34][35]. In our study the prevalence of hyperferritinemia was significantly higher in the NASH patients than in patients with simple steatosis.…”
Section: Discussioncontrasting
confidence: 66%
“…Many previous studies conducted in predominantly Caucasian populations suggested that HFE mutations are more common among patients with NASH or NAFLD, compared to control populations, implicating HFE as a susceptibility locus for this disease [3,8,[71][72][73][74]. Not surprisingly, HFE mutations were infrequent among NASH cohorts in the non-Caucasian populations of Brazil [75], Japan [76,77], Taiwan [78] and India [79,80]. However, a recent study suggests that H63D HFE mutations may be more prevalent among Koreans with NAFLD than control subjects [81].…”
Section: The Role Of Mutations In Hfe and Other Hepcidin Regulatory Gmentioning
confidence: 89%
“…Similarly, none of the patients with NAFLD/NASH in Japan was found to have HFE gene mutations. 95 In a multiethnic study from Australia, only Anglo-Celtic patients were found to have increased C282Y heterozygosity in NASH compared with controls, although it did not predict for disease severity or fibrosis. None were homozygous for the mutation.…”
Section: Patatin-like Phospholipase Domain-containing Protein 3 and Nmentioning
confidence: 97%